Thermospheric density variations during extreme geomagnetic storms and their potential impact on the orbit of the China space station - Zhang, Kun; Huang, Yanshi; Wei, Fengsi; Zuo, Pingbing; Yang, Hao; Ji, Jinlong; Chen, Zehao (Frontiers in Astronomy and Space Sciences, 2025)
Temporal variation and spatial distribution of the thermospheric density can change significantly during geomagnetic storms. These variations in thermospheric density enhance atmospheric drag, posing risks to Low-Earth-Orbit (LEO) spacecraft. Therefore, studying the characteristics of intense storm-time thermospheric density perturbations and orbit decay is crucial for practical applications. In this study, neutral density was simulated for the strongest magnetic storm events of solar cycles 24, 23, and 22, corresponding to minimum Dst indices of −234 nT (2015 St. Patrick’s Day storm), −442 nT (20 November 2003 storm), and −598 nT (1989 Quebec blackout storm). Four representative thermospheric models (DTM-2020, JB 2008, NRLMSIS 2.0, and TIEGCM 2.0) were employed to evaluate their performance during extreme geomagnetic storms by comparing simulated densities with satellite observations from Swarm, CHAMP, and GRACE during the November 2003 and March 2015 storm events. The results indicate that the errors of all models exhibit larger errors in the main and recovery phases, with a bias toward underestimation of density during the main phase. It is important to note that no thermospheric model is perfect and each model has its own limitations, especially dealing with extreme space weather events. Although JB2008 performs relatively well, it does not maintain the best performance across all phases, and its predictions still deviate from observations by at least 20%. Therefore, combining multiple model outputs is recommended for extreme cases. Furthermore, these thermospheric models were coupled with the High-Precision Orbit Propagator (HPOP) to examine the orbital decay of the China Space Station (CSS, ∼380–400 km altitude) during these events. The effects of drag on CSS during the strongest magnetic storm events in the 24th, 23rd and 22nd solar cycles were simulated. The orbital decay is about 233%, 300% and 266% higher than that in the quiet period, respectively. The reults of this study might serve as a reference for spacecraft for possible upcoming extreme magnetic storm events.